Multi-active-area tunnel cascade resonant cavity red light Micro-RC LED - LI JIANJUN; REN KAIBING (2022)
The invention discloses a multi-active-area tunnel cascade red light Micro-RCLED based on a resonant cavity, and belongs to the technical field of semiconductor electronics. The laser comprises an upper electrode, an upper Bragg reflector, a resonant cavity, a lower Bragg reflector, a substrate and a lower electrode from top to bottom. Wherein the upper Bragg reflector consists of a material layer with a relatively high refractive index and a material layer with a relatively low refractive index; the resonant cavity is composed of a plurality of active regions, and each active region comprises a reverse bias tunnel junction, a matching layer, an oxidation limiting layer, an upper limiting layer, a quantum well and a lower limiting layer; the lower Bragg reflector is composed of a material layer with a relatively high refractive index and a material layer with a relatively low refractive index. Cascade connection of multiple active areas is achieved through the reverse bias tunnel junction, the internal quantu